Race/ethnicity-stratified fine-mapping of the MHC locus reveals genetic variants associated with late-onset asthma - Lee, Eunice Y.; Choi, Wonson; Burkholder, Adam B.; Perera, Lalith; Mack, Jasmine A.; Miller, Frederick W.; Fessler, Michael B.; Cook, Donald N.; Karmaus, Peer W. F.; Nakano, Hideki; Garantziotis, Stavros; Madenspacher, Jennifer H.; et al. (Frontiers in Genetics, 2023)
Asthma is a chronic disease of the airways that impairs normal breathing. The etiology of asthma is complex and involves multiple factors, including the environment and genetics, especially the distinct genetic architecture associated with ancestry. Compared to early-onset asthma, little is known about genetic predisposition to late-onset asthma. We investigated the race/ethnicity-specific relationship among genetic variants within the major histocompatibility complex (MHC) region and late-onset asthma in a North Carolina-based multiracial cohort of adults. Methods. We stratified all analyses by self-reported race (i.e., White and Black) and adjusted all regression models for age, sex, and ancestry. We conducted association tests within the MHC region and performed fine-mapping analyses conditioned on the race/ethnicity-specific lead variant using whole-genome sequencing (WGS) data. We applied computational methods to infer human leukocyte antigen (HLA) alleles and residues at amino acid positions. We replicated findings in the UK Biobank. Results. The lead signals, rs9265901 on the 5’ end of HLA-B, rs55888430 on HLA-DOB, and rs117953947 on HCG17 were significantly associated with late-onset asthma in all, White, and Black participants, respectively [OR = 1.73, 95%CI: 1.31 to 2.14, P = 3.62×10-5; OR = 3.05, 95%CI: 1.86 to 4.98, P = 8.85×10-6; OR = 19.5, 95%CI: 4.37 to 87.2, P = 9.97×10-5, respectively]. For the HLA analysis, HLA-B*40:02 and HLA-DRB1*04:05, HLA-B*40:02, HLA-C*04:01, and HLA-DRB1*04:05, and HLA-DRB1*03:01 and HLA-DQB1 were significantly associated with late-onset asthma in all, White, and Black participants. Conclusion. Multiple genetic variants within the MHC region were significantly associated with late-onset asthma, and the associations were significantly different by race/ethnicity group.